Alternative pre-mRNA splicing of Toll-like receptor signaling components in peripheral blood mononuclear cells from patients with ARDS - Blumhagen, Rachel Z.; Hedin, Brenna R.; Malcolm, Kenneth C.; Burnham, Ellen L.; Moss, Marc; Abraham, Edward; Huie, Tristan J.; Nick, Jerry A.; Fingerlin, Tasha E.; Alper, Scott (American journal of physiology. Lung cellular and molecular physiology, 2017)
A key physiological feature of acute respiratory distress syndrome (ARDS) is inflammation. Toll-like receptor (TLR) signaling is required to combat the infection that underlies many ARDS cases but also contributes to pathological inflammation. Several TLR signaling pathway genes encoding positive effectors of inflammation also produce alternatively spliced mRNAs encoding negative regulators of inflammation. An imbalance between these isoforms could contribute to pathological inflammation and disease severity. To determine whether splicing in TLR pathways is altered in patients with ARDS, we monitored alternative splicing of MyD88 and IRAK1, two genes that function in multiple TLR pathways. The MyD88 and IRAK1 genes produce long proinflammatory mRNAs (MyD88 L and IRAK1) and shorter anti-inflammatory mRNAs (MyD88 S and IRAK1c). We quantified mRNA encoding inflammatory cytokines and MyD88 and IRAK1 isoforms in peripheral blood mononuclear cells (PBMCs) from 104 patients with ARDS and 30 healthy control subjects. We found that MyD88 pre-mRNA splicing is altered in patients with ARDS in a proinflammatory direction. We also observed altered MyD88 isoform levels in a second critically ill patient cohort, suggesting that these changes may not be unique to ARDS. Early in ARDS, PBMC IRAK1c levels were associated with patient survival. Despite the similarities in MyD88 and IRAK1 alternative splicing observed in previous in vitro studies, there were differences in how MyD88 and IRAK1 alternative splicing was altered in patients with ARDS. We conclude that pre-mRNA splicing of TLR signaling genes is altered in patients with ARDS, and further investigation of altered splicing may lead to novel prognostic and therapeutic approaches.